If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -40 + -2b = -2 + 2(1 + -5b) -40 + -2b = -2 + (1 * 2 + -5b * 2) -40 + -2b = -2 + (2 + -10b) Combine like terms: -2 + 2 = 0 -40 + -2b = 0 + -10b -40 + -2b = -10b Solving -40 + -2b = -10b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '10b' to each side of the equation. -40 + -2b + 10b = -10b + 10b Combine like terms: -2b + 10b = 8b -40 + 8b = -10b + 10b Combine like terms: -10b + 10b = 0 -40 + 8b = 0 Add '40' to each side of the equation. -40 + 40 + 8b = 0 + 40 Combine like terms: -40 + 40 = 0 0 + 8b = 0 + 40 8b = 0 + 40 Combine like terms: 0 + 40 = 40 8b = 40 Divide each side by '8'. b = 5 Simplifying b = 5
| 56=4x | | w^25= | | A(x-2)(x-3)= | | 2+m=-10 | | 6x+9=-108-7x | | -8q-3(q+4)=q+7 | | 6x+9=-1008-7x | | x-(-3)=-1 | | -4y-13=9y+13 | | -3+9x=3(x+6) | | 18b=-234 | | 2x+30=12x | | 3c+c=48 | | 4q+2(-8+3q)=3 | | 8x-73=3x-13 | | 3x-7=7x-9 | | -11n=99 | | 2-5v-6v=2 | | 2-5v-6v=23 | | 12-7x=144-35x | | 42=-3(4n-2) | | -p-8p=3-6p | | -32=-2v | | -2a+5=5 | | 6(2x-9)=-102 | | -4n=-n-6 | | 7x^2-6= | | -39x+31=225 | | -12=-x-5x | | 8x+3=9+5x | | 6=14+n | | 3(5+3x)=-3(6-2x) |